Research Trends Material Physics E-Module Based on Synthesis and Characterization of Barium M-Hexaferrite using PjBL Model to Enhance Student Creativity (A Review) - Susilawati; Kosim; Nisa Hidayatullah; Syarful Annam (Postgraduate, University of Mataram, 2026)
This study aims to map and synthesize existing research related to PjBL-based e-modules, student creativity, and BaM hexaferrite material studies, in order to identify research trends, gaps, and opportunities for interdisciplinary integration. A Hybrid Review methodology was employed, combining a Systematic Literature Review (SLR) guided by PRISMA 2020 and a Bibliometric Review. Literature published between 2018 and 2025 was collected from Scopus and SINTA databases. A total of 38 eligible articles were included for qualitative synthesis and bibliometric mapping. The SLR examined research focus, methodologies, learning outcomes, and material synthesis approaches, while the bibliometric analysis explored publication trends, keyword co-occurrence, collaboration networks, and thematic structures. The results indicate that PjBL-based e-modules are consistently effective in fostering creativity and higher-order thinking skills. However, bibliometric evidence reveals a clear separation between physics education research and BaM hexaferrite material studies, with minimal thematic overlap. This finding highlights a significant research gap and underscores the novelty of integrating BaM hexaferrite synthesis and characterization into a PjBL-oriented e-module. The study provides a strong conceptual foundation for developing research-based digital learning materials that promote authentic scientific creativity in higher education physics.